Gender and Translation - Khotimah, Emy Rahmawati Isfatin (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
This study explores the ideological influences of gender on translation practices by examining how male and female translators approach and translate texts differently. Through qualitative analysis of translated works and interviews with the translators, the writer investigates the underlying beliefs, cultural contexts, and personal experiences that shape their translation choices. The findings reveal distinct patterns in handling nuances, tone, and stylistic elements, highlighting how gender may inform translators’ ideologies and the resulting implications for fidelity and creativity in translation. Ultimately, this research contributes to a deeper understanding of the intersection between gender and translation, suggesting that awareness of these ideological factors can enhance translation studies and practices.